JAPANESE CARTOON FENCER BUILDING CHARACTERS USING CorelDRAW 12.0 - Hadi Firdaus (Jurnal Sistem Informasi, 2007)
The development of computer technology so rapidly, the initial function as a tool insolving issues and problems in all fields and then enter the function as an entertainer. It ismarked with many products in the world of computer-based entertainment. One of theentertainment world is much in demand is a comic or cartoon. The use of computers toproduce a professional cartoon was done starting with the cartoons that made Hollywoodthe United States that use computerized. Making computerized cartoons provide manybenefits to the animator since with the help of software that has special tools to givecertain effects that can not be created manually. With these cartoons make more livelyand interesting. In making this application the author using CorelDraw 12 program.